2023
DOI: 10.1097/md.0000000000033110
|View full text |Cite
|
Sign up to set email alerts
|

Patatin-like phospholipase domain-containing 3 gene (PNPLA3) polymorphic (rs738409) single nucleotide polymorphisms and susceptibility to nonalcoholic fatty liver disease: A meta-analysis of twenty studies

Abstract: Background: To investigate the correlation between rs738409 polymorphism of patatin-like phospholipase domain-containing protein 3 (PNPLA3) gene (encoding I148m) and genetic susceptibility to nonalcoholic fatty liver disease (NAFLD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Previous meta-analyses have consistently shown an association between the PNPLA3 G allele and the onset/severity of MASLD. 22,23 However, these meta-analyses mainly evaluated PNPLA3 variant-related associations without adopting formal adequate inclusion criteria to minimize the risk of selection bias. Compared with these meta-analyses, we used stringent inclusion criteria for MASLD patients and analyzed more studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous meta-analyses have consistently shown an association between the PNPLA3 G allele and the onset/severity of MASLD. 22,23 However, these meta-analyses mainly evaluated PNPLA3 variant-related associations without adopting formal adequate inclusion criteria to minimize the risk of selection bias. Compared with these meta-analyses, we used stringent inclusion criteria for MASLD patients and analyzed more studies.…”
Section: Discussionmentioning
confidence: 99%
“…3 Recent advances have shed light on genetic variations linked to MASLD, 4 with a spotlight on the rs738409 C > G (p.I148M) single nucleotide polymorphism in the patatin-like phospholipase domain-containing protein-3 (PNPLA3) gene, identi ed as a prominent genetic risk factor across the spectrum of MASLD. [5][6][7] In particular, the interplay of this genetic factor with both treatment and environmental factors has attracted considerable scienti c interest 8,9 in a discussion centered on the potential usefulness of PNPLA3 genotyping to guide MASLD management. 10 Despite these advances, the genetic epidemiology of PNPLA3 in MASLD patients and the extent of its impact on disease phenotype, as well as potential variations due to environmental factors, remain uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…This variation in disease progression suggests genetic predispositions and, indeed, studies have shown that genetic factors play a role in NAFLD pathogenesis 12 13 . Although a polygenic disease, common genetic variants have been consistently associated with increased risk of steatosis, particularly small nucleotide polymorphisms (SNPs) in Patatin-like phospholipase domain-containing protein 3 ( PN P LA3 ), Lysophospholipase-like 1 ( LYPLAL1 ), protein phosphatase 1 regulatory subunit 3B ( PPP1R3B ), Neurocan ( NCAN ) and glucokinase regulator ( GCKR ) 14 15 16 . However, an accumulation of fat is not the only risk factor for promoting the transition from non-alcoholic fatty liver to NASH, a central component is persistent inflammation 4,5 .…”
Section: Introductionmentioning
confidence: 99%